1992
DOI: 10.1111/j.1399-302x.1992.tb00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid production by streptococci growing at low pH in a chemostat under anaerobic conditions

Abstract: Streptococcus mutans and other oral streptococci were grown in continuous culture under strictly anaerobic conditions. When the cultural pH was kept at 7.0, the main acid products were formate and acetate, as reported previously. However, more lactate was produced at pH values of 5.5 or 6.0, with a concomitant decrease in formate and acetate production. This change in fermentation products could partly be ascribed to a change in intracellular pH and difference in the pH optima between pyruvate formate-lyase (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 21 publications
5
57
0
3
Order By: Relevance
“…Studies of changes in the levels of protein expression, along with measurement of the final by-products of carbon utilization, Y Glc and Y ATP , have confirmed previous findings that streptococci tolerate growth at pH 5?0 by increasing their ability to extrude H + , while modulating the production of acid fermentation by-products to reduce the level of H + production (Hamilton, 1984;Iwami et al, 1992;Miyagi et al, 1994). The results further suggest that S. mutans utilizes branched-chain amino acid biosynthesis to lower the amount of reducing equivalents in the form of NAD(P)H that would otherwise be converted to acidic by-products, and by so doing helps buffer the cytoplasm by producing NH 3 .…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Studies of changes in the levels of protein expression, along with measurement of the final by-products of carbon utilization, Y Glc and Y ATP , have confirmed previous findings that streptococci tolerate growth at pH 5?0 by increasing their ability to extrude H + , while modulating the production of acid fermentation by-products to reduce the level of H + production (Hamilton, 1984;Iwami et al, 1992;Miyagi et al, 1994). The results further suggest that S. mutans utilizes branched-chain amino acid biosynthesis to lower the amount of reducing equivalents in the form of NAD(P)H that would otherwise be converted to acidic by-products, and by so doing helps buffer the cytoplasm by producing NH 3 .…”
Section: Discussionsupporting
confidence: 57%
“…The levels of the final three enzymes in glycolysis at pH 5?0 were consistent with a reduced pool of phosphoenolpyruvate, since the reduced levels of enolase, in conjunction with an overall 2?8-fold increase in the four isoforms of pyruvate kinase, would be expected to convert 2-phosphoglycerate to pyruvate without any build-up of phosphoenolpyruvate. This idea is supported by the measurement of the four intermediates, 3-phosphoglycerate, 2-phosphoglycerate, phosphoenolpyruvate and pyruvate, in S. mutans grown at pH 5?5 and D=0?15 h 21 , where the levels of 3-phosphoglycerate and phosphoenolpyruvate decrease, that of 2-phosphoglycerate remains static and the amount of pyruvate increases (Iwami et al, 1992). This is further supported by another study, where a fall in intracellular pH was shown to significantly increase the pyruvate : phosphoenolpyruvate ratio (Iwami & Yamada, 1980).…”
Section: Glycolysismentioning
confidence: 57%
See 3 more Smart Citations